HUBUNGAN ANTARA KETERAMPILAN METAKOGNITIF DAN PEMAHAMAN KONSEP BIOLOGI SISWA KELAS X PADA PENERAPAN STRATEGI PROBLEM-BASED LEARNING DAN RECIPROCAL TEACHING DI SMA BRAWIJAYA SMART SCHOOL MALANG - Abdul Basith; Aloysius Duran Corebima; Siti Zubaidah (Universitas Sebelas Maret, 2014)
The objectives of the research are (1) the disclose the relationship between metacognitive skill and biology concept understanding of Grade X student during the application of PBL and RT strategies and (2) to illustrate the different regression equation between metacognitive skill and biology concept understanding of Grade X students during the application of PBL and RT strategies. The population of this research is all of Grade X students at SMA Brawijaya Smart School Malang. The sample of research is X-3 class for application of PBL strategy and X-5 class for application of RT strategy. The application of learning strategies implemented for 10 weeks on the Monera, Protista, and Fungi material. Data collection was performed before and after each application of learning strategies. Metacognitive skill measured with special rubric of metacognitive that integrated with achievement test developed by Corebima (2009), while understanding the biological concept of learning outcomes measured by the rubric of biology. Result of research indicates that (1) there is positive relationship between metacognitive skill and biology concept understanding during the application of PBL and RT strategies in orderen manner 81,6% and 66,7% and (2) PBL and RT have same potential to improve metacognitive skill and also biology concept understanding and it form a line pattern which matches with regression equation and the line is closely parallel and coincide.Keywords: Problem-based Learning Strategy, Reciprocal Teaching strategy, metacognitive skill, biology concept understanding